Studies on the Possible Bioaccumulation of Heavy Metals in Soil Samples Dumped With Faecal Sludge - M. K, Salamatu; S, Modu; G, Chamba; B. P., Bintu; M. A, Hamsatu; A. S., Falmata (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Heavy metal pollution has become a growing environmental concern primarily due to human activities. While it is found in soils naturally through processes of weathering of parent materials, it is the anthropogenic activities that create the greatest threat. This study was carried out to determine the possible bioaccumulation of heavy metals in faecal sludge, soil and maize grown on faecal dumped farm. The samples (faecal sludge, soil and maize) were obtained from University of Maiduguri Farm, Borno State, at three different depths (0cm, 10cm, 20cm and 30cm). Heavy metals were analyzed using standard method. In this study, spatial variations were observed for all metals across the depth. The results of the pH of the soil in this study ranged from 5.78 to 7.54. The results showed that heavy metals are more concentrated at 10cm and 20cm depth of the test soil with pH values of 5.78 and 5.92 respectively. The concentration of heavy metals at 0cm depth were Nickel (2.17 mg/kg), Cobalt (1.11mg/kg), Selenium (0.81mg/kg), Arsenic (0.21mg/kg), Lead (2.19mg/kg), Cadmium (5.61mg/kg), Mercury (0.70mg/kg), Chromium (8.72mg/kg), Zinc (5.48mg/kg) and Iron (13.03mg/kg) having the lowest concentration of metals. The concentration of heavy metals determined in faecal sludge in this study were in the sequence Cr>Zn>Pb>Ni>Cd>Fe>Se>As>Co>Hg. Selenium and Cadmium content of the test soil were above the recommended WHO limit of 0.3mg/kg for selenium and 0.5mg/kg for cadmium at all depths. The level of Cr and Hg were above permissible limit only at depth 10cm, surpassing the permissible limit set by WHO 2021 of 30-50 mg/kg and 0.3 mg/kg for Cr and Hg respectively for soil’s maximum heavy metals limit. Nickel, Cobalt, Arsenic, Lead, Zinc and Iron of the test soil were within the permissible limit. Selenium at all depths 0cm (0.7 mg/kg), 10cm (1.33 mg/kg), 20cm (0.63 mg/kg), 30cm (0.50 mg/kg) and Cd 0cm (4.91 mg/kg), 10cm (6.56 mg/kg), 20cm (15.31 mg/kg), 30cm (8.40 mg/kg) at the control soil were above the permissible limit of 0.3mg/kg for Se and 2.0mg/kg for Cd in the soil while Ni, As, Pb, Hg, Cr, Zn and Fe were also within the permissible limit. In conclusion, regular monitoring and testing of soil, water and crops should be conducted to ensure compliance with safety standards and prevent heavy metal contamination.